Influência do consumo de farinha de casca e semente de lichia (Litchichinensis Sonn) sobre o estresse oxidativo e perfil cardiometabólico de ratos obesos induzidos ao diabetes - Coelho, Priscila Murucci (2018)
Introduction: Overweight and obesity are important risk factors for the development of type 2 diabetes. Excess weight associated to type 2 diabetes mellitus promotes high risk for the development of cardiovascular diseases. Although the literature suggests that oxidative stress is related to diabetic cardiomyopathy, the mechanism of generation of reactive oxygen species is still not well understood. Thus, foods with a high level of antioxidant compounds may be beneficial in preventing and/or reversing OE in obese diabetic. Studies have shown that both the extract and flour of lychee peel and seed are rich in phenolic antioxidant compounds. Objective: To evaluate the flour consumption of seed and peel lychee on oxidative stress, metabolic and cardiomyocyte contractile function in diabetic obese rats. Methodology: Male Wistar rats were submitted to obesity condition by high-fat diet, and and subsequently induced to type 2 Diabetes Mellitus. Then, the animals were randomized into groups: Obese (Ob, n=10), Diabetic obese (ObD, n=8), Diabetic obese treated with lychee peel flour (ObDPF, n=10) and Diabetic obese treated with lychee seed flour (ObDSF, n=10). Nutritional and glycemic profiles, water contente of lung and liver, pancreas weight, and serum oxidative stress parameters were performed. Furthermore, the total weight of the heart and its relation to tibia length were analyzed. Cardiomyocytes contractile function was assayed. Data were expressed as mean ± standard deviation or median ± interquartile range. The comparisons were performed by student’s t test or one-way ANOVA and complemented by Bonferroni and Dunn’s post hoc tests. The level of significance was 5%. Results: ObD presented lower body weight, fat pads and pancreas weight in relation to Ob, on the other hand, there was enhanced of protein carbonylation andsuperoxide dismutase levels. Regarding the cardiomyocyte contractile function, ObD presented higher systolic Ca2+ with percentual elevation of shortening, in contrast, there was greater time to peak 50% of shortening. On the other hand, although ObD rats presented higher maximal velocity of relaxation, there was elevation of diastolic Ca2+ levels and greater time to peak 50% of recapture. The treatments with flour of seed and peel lychee did not able to change body and morfologic parameters, and biomarkers of oxidative stress in ObD. The ObDPF triggered elevation time to peak 50% of shortening compared to ObD rats, without modifications in relaxation contractile parameters. However, the ObDSF presented reduction of percentual and maximal velocity of shortening with consequently increased in time to peak 50% of shortening in relation to ObD.Although diastolic Ca2+ levels were lower in ObDFS rats, there was no significant difference (p = 0.056). .Between the ObDSF and ObDPF treatments, results showed that ObDSF presented lower maximal velocity of relaxation, concomitant to higher time to peak 50% of recapture. Conclusion: The flour of seed and peel lychee did not revert the oxidative damage and the contractile injury in cardiomyocytes of obese rats induced to diabetes. In addition, the flour of seed lychee accentuated the contractile dysfunction without changes in intracellular Ca2+ handling.